Pengajaran Bahasa Inggris bagi Siswa SD Persiapan Menuju Desa Aan sebagai Smart Village - Ni Wayan Mekarini; Ni Nyoman Ardani; I Putu Raditya; I Made Agung Rai Antara; Komang Shintya Nita Kristina Putri; I Made Sunata; Putu Asda Ryawan (Prosiding Seminar Nasional Riset dan Pengabdian pada Masyarakat, 2024)
The Thematic Social Services is one of students' sercices to the community to implement the Tri Darma of Higher Education by doing certain contributions to society. Triatma Mulya University held social services program in some villages in Bali and one of them done in Aan Village, Banjarangkan District, Klungkung Regency, Bali for 5 weeks from 08 January 2024 to 06 February 2024 with the theme "Community-Based Village Potential Development towards Smart Village". One of the sub-themes promoted is "Teaching Elementary Level Students", in order to build bright generation that has competencies according to the needs of tourist villages, including the ability to master English. English language teaching is carried out at both SD Negeri 1 Aan and SD Negeri 2 Aan. This teaching program not only focuses on academic aspects, but also stimulates student creativity through a program of modifying texts according to actual conditions as well as producing similar text. The success of the teaching program can be seen from the participation and enthusiasm of students in participating in each activity. In general, the Aan Village KKNT program not only provides benefits to the local community, but also becomes a forum for the team to implement knowledge and skills in working together and coordinating with stakeholders as a form of positive contribution to overall community development.